(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines current trends in the transformation of reading practices in the context of the digitalization of education. It analyzes changes in the perception and consumption of information by students, the transition from traditional printed books to electronic educational resources, and the role of university libraries in shaping a digital learning environment. The study identifies the advantages and limitations of a university’s electronic resources and outlines promising directions for the development of digital reading in higher education.